COACHING ADVENTURE SPORTS - Smith, Paul; Wilkinson, Dan (Adventure Sports Media House, 2020)
This book takes a look at the specific challenges faced by Adventure Sports Coaches It examines how to put theory into practice. Content accords with a range of recent academic research, and each chapter contains suggestions for further reading.